Menstrual Irregularities and its Awareness in the Students of Sir Syed Medical College for Girls Karachi (Journal of Fatima Jinnah Medical University, 2018)
Objective: To assess the Menstrual Irregularities and its awareness in students of Sir Syed Medical College for girls in Karachi. Study Design: It was an analytical cross sectional study. Place And Duration: The study was carried out on students of Sir Syed Medical College for Girls from August 2012 – January 2013. Material and Methods: A total of 240 students were included in the study. A detail Proforma was given to them after a verbal consent acquired from the authorities of the ethical committee. Moreover all individual were quierd in centered confidential to reduce influence from other people. Information was collected in both Urdu and English but proforma was filled in English. A data collection form with respect to age, demographic data, history of menstrual cycle, interval of days, Dysmenorrhea, flow pattern, family history, comorbidities were collected. Biochemical evaluation was also analysed. Results: The study conducted on students of our college showed that out of the 240 students 167 (69.5%) had menstrual irregularities whereas 30% did not. The average age of menarche was 12.5 years. The duration of cycle was 5.2 days on an average. In our study majority 42% had cycle interval between 20 – 25 days. Dysmenorrhea was present in 51.6% of our students. The pattern of flow was moderate in 50% however in 33% it was heavy flow. Majority of the students had no intermenstrual bleeding and 35.83% had intermenstrual bleeding. The number of pads soaked in our study on an average was 4 – 5 pads. Majority of girls 37.08% having family history of Menstrual Irregularities of which Polycystic Ovarian disease being one of the leading cause i.e. 17.92%. Conclusion: The results highlighted that Menstrual Irregularities were common in young females. However that awareness of menstrual irregularities makes living with one easier.
Keywords: Medical Students, Menstrual Irregularity, Menarche, Dysmenorrhea.